Knowledge Externalities, Innovation Clusters and Regional Development 2007
DOI: 10.4337/9781847207173.00010
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalent Role of Mimetic Behavior in Proximity Dynamics: Evidence from the French ‘Silicon Sentier’

Abstract: Le rôle ambivalent des comportements mimétiques dans les dynamiques de proximité : évidences à partir du « Silicon Sentier » français Résumé Cet article examine le rôle des comportements mimétiques dans les processus de colocalisation. Nous montrons que la proximité géographique n'est pas une condition nécessaire et suffisante de la performance collective des clusters. D'autres types de proximités caractérisent les clusters, et, parmi les nombreuses voies d'analyses des clusters, nous montrons que l'approche p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Mimetic behaviours have been observed frequently over short geographic distances (Bell, 2005;Burt, 1987;Greve, 1998;Staber, 2010;Vicente et al, 2006). For example, Greve (1998) found that a market position adoption is likely to be imitated in a geographically proximate market.…”
Section: Mimetic Behaviour and International Alliance Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mimetic behaviours have been observed frequently over short geographic distances (Bell, 2005;Burt, 1987;Greve, 1998;Staber, 2010;Vicente et al, 2006). For example, Greve (1998) found that a market position adoption is likely to be imitated in a geographically proximate market.…”
Section: Mimetic Behaviour and International Alliance Formationmentioning
confidence: 99%
“…In an emerging context, it would be more rational to imitate agents than to spend time and money seeking solutions and testing them. These early mimetic behaviours, which also provide the rationale for the firm's location choice (Vicente et al, 2006), give way to new, more autonomous behaviours (Pourder and St John, 1996). This suggests that cluster age moderates a firm's mimetic behaviour, making it less salient in older clusters.…”
Section: Cluster Evolution and International Alliance Formationmentioning
confidence: 99%
“…These may facilitate knowledge sharing and other forms of cooperation; studies of such forms of proximity tend to point to a largely indirect role for the spatial dimension in fostering knowledge creation, interactive learning and innovative networks by bridging and reinforcing other forms of propinquity (e.g. Kirat and Lung, 1999;Nooteboom, 1999;Torre and Gilly, 2000;Boschma, 2005;Torre and Rallet, 2005;Moodysson and Jonsson, 2007;Ponds et al, 2007;Vicente et al, 2007;Balconi et al, 2011).…”
Section: Factors Moderating the Role Of Geographical Proximitymentioning
confidence: 99%
“…Therefore, quantitative data, as well as methods, in particular statistics and surveys, dominate the field. Vicente et al (2007) Interviews Balconi and Laboranti (2006) Interviews, patent data Menzel (2008) - Spila et al (2008) -In this paper, it is argued that there is a call for studying CP as a process and at the group level. Thus, qualitative materials and methods with a case study approach are needed.…”
Section: Cognitive Proximity In Current Studiesmentioning
confidence: 98%
“…Yet, some studies do not clearly explain what this knowledge base may be (e.g. Aslesen and Jakobsen, 2007;Boschma, 2005;Boschma and Frenken, 2009;Sternberg, 2007;Vicente et al, 2007), giving rise to criticism of CP for not being clear enough (Knoben and Oerlemans, 2006). Many of the empirical studies compare knowledge bases through standard statistical classifications, when companies who are operating or patenting in the same sectors share similar knowledge bases and are cognitively proximate (Boschma and Iammarino, 2009;Broekel and Boschma, 2009;Brossard and Vicente, 2007;Nooteboom et al, 2007).…”
Section: Cognitive Proximity In Current Studiesmentioning
confidence: 99%